Oligopeptide Helical Conformations Control Gold Nanoparticle Cross‐Linking. Issue 50 (13th August 2019) - Lyu, Yanchao; Marafon, Giulia; Martínez, Álvaro; Moretto, Alessandro; Scrimin, Paolo
Abstract: Peptide sequences functionalized with primary amines at the N‐ and C‐terminus are able to induce the aggregation of gold nanoparticles in ethanol as a consequence of their folding into a helical conformation. Random coil peptides are unable to induce such an aggregation process. Aggregation can be monitored spectrophotometrically by following the shift of the surface plasmon resonance (SPR) band of the nanoparticles and is confirmed by transmission electron microscopy and dynamic light scattering analyses. Partial denaturation of the peptides results in diminished cross‐linking ability. The helicity parameter θ 222 / θ 208 correlates fairly well with the shift of the SPR band to longer wavelengths, supporting the relationship between the amount of helical content of a peptide sequence and its ability to induce aggregation. Abstract : Short peptide foldamers induce gold nanoparticle aggregation in ethanol, through a cross‐linking process, whereas their random‐coil counterparts do not. The process can be followed by monitoring the shift of the surface plasmon resonance band to a longer wavelength and the increase of the apparent hydrodynamic diameter of the formed aggregates in dynamic light scattering experiments.